Ivanova pisma Micki - izseljenska zgodba - Janežič, Helena (2018)
Marija Krek was born in 1906 near Škofja Loka, in today's Slovenia; at that time, it was a part of the Kingdom of the Serbs, Croats, and Slovenes. With her mother, brother and sister she left for America in 1921, to join their father who had gone there a few years before; he had settled in Yankee, a small mining town in New Mexico. When Marija (Micka, Mici) came into the Promised Land, she became Mary. Soon after her arrival, she began working at the hotel and restaurant owned by her uncle. At an entertaining Sunday event, she was noticed by Ivan Bizjak, a Slovene from Dawson. He was born in 1894 in Osp, a village in the Coastal–Karst region, situated on the Slovenian ethnic territory, which at that time belonged to the Kingdom of Italy. Ivan also came to America in 1921 from Trieste.Ivan and Mary married on 7 June 1924, after the bride had attained the age of 18 years. In the meantime, wonderful love letters were travelling between Yankee and Dawson - now abandoned "ghost towns”; they were written in Slovenian, their mother tongue. Unfortunately, only Ivan’s letters are preserved.
Marija Krek was born in 1906 near Škofja Loka, in today's Republic of Slovenia; at that time, it was a part of the Kingdom of the Serbs, Croats, and Slovenes. With her mother, brother and sister she left for America in 1921, to join their father who had gone there a few years before; he had settled in Yankee, a small mining town in New Mexico. When Marija (Micka, Mici) came into the Promised Land, she became Mary.Soon after her arrival, she began working at the hotel and restaurant owned by her uncle.  At an entertaining Sunday event, she was noticed by Ivan Bizjak, a Slovene from Dawson. He was born in 1894 in Osp, a village in the Coastal–Karst region, situated on the Slovenian ethnic territory, which at that time belonged to the Kingdom of Italy. Ivan also came to America in 1921 from Trieste.Ivan and Mary married on 7 June 1924, after the bride had attained the age of 18 years. In the meantime, wonderful love letters were travelling between Yankee and Dawson - now abandoned "ghost towns”; they were written in Slovenian, their mother tongue.Unfortunately, only Ivan’s letters are preserved.